Covid-1999 reflections on world agricultural commodity prices and their impact on food prices with path analysis model - Bilal Najah Al-jobir; Sara Qassem Ajil (Dirassat Journal Economic Issue, 2022)
The world has faced major challenges over the corona epidemic, and the effects of the pandemic have been reversed on all economic sectors, not only the agricultural sector but also the most vulnerable sectors. The pandemic and its accompanying health measures have disrupted agricultural production by stalling access to fertilizers and pesticides in a timely manner, as well as the transfer of agricultural products to consumption sites, The pandemic also led to higher prices for production components, especially imported ones, such as seeds, fertilizers, and pesticides, which led to higher prices for agricultural commodities and food prices in general. The aim of this study was to study the impact on the price fluctuations of agricultural goods and their impact on higher food prices. These effects are among the basic reasons why researchers study and reflect these fluctuations.